Synthesis TiO2 -SiO2 Composites Using The Method Sol-Gel-Hydrothermal - Milawati, Sri; Syahbanu, Intan; Sasri, Risya (Jurnal ILMU DASAR, 2021)
Titanium dioxide (TiO2) is a transition metal oxide material which has been researched extensively and can be used for various applications. In this research, synthesis of TiO2 -SiO2 using TTIP and TEOS precursor. Research aims to determine the characteristics of composite materials generated based on the influence of hydrothermal time and precursor composition. Synthesis is done by variation of hydrothermal time (4 hours, 8 hours, 18 hours, 24 hours and without hydrothermal) and TEOS precursor composition variation (1:1, 1:2 and 2:1). Synthesis is made by dissolving the two precursors through the sol-gel-hydrothermal method and continued with the calcination process. Characterization using FT-IR showed a bonding Ti-O-Si at a wavelength of 950 cm-1 . This bond is formed from the interaction between TiO2 and SiO2 which indicates the success of the synthesis. The XRD characterization results show formed of a peak at 2θ° the range 25° for all composites. The results of the dr-uv characterization on the TiO2 -SiO2 composite comparison of 2:1 showed absorption at 387 nm and obtained band gap energy of 3,20 eV. Based on the data obtained it can be concluded that synthesis of TiO2-SiO2 hydrothermally obtained the optimum time 24 hours and the best comparison is contained in the composition 2:1, which produces an anatase structure with a crystal size of 15,899 nm, so that the resulting composite can be used as a photocatalyst. Keywords: Hydrothermal, Sol-gel, TiO2 -SiO2.